Evaluation of the Use of Cloud-Technologies in Russian Banks During the Crisis - Bataev, Alexey V. (International Journal of Economics and Financial Issues, 2017)
The paper considers consequences of the global economic crisis and the Western sanctions imposed on the banking system of Russia. Banks have to decrease the expenses in the conditions of limited access to financial resources and decline in business activity. Cost reduction by financial institutions can be provided going to innovative models of the development, therefore the article discusses the possibility of Russian banks to use cloud technologies. The tendencies and perspectives of the Russian and global cloud computing market development, the basic model of cloud services are reviewed. The analysis of the factors are not allowing to provide rapid implementation of cloud-technologies in the Russia’s banking sector is carried out. Keywords: economic crisis, cloud computing, Internet technology, financial institutions, the types of cloud services JEL Classifications: G01, G21, O33